Modern view on hepatic encephalopathy: basic terms and concepts of pathogenesis - T. V. Shulyatnikova; V. A. Shavrin (Zaporozhye State Medical University, 2017)
Background. The problem of acute and chronic forms of hepatic encephalopathy (HE) is not clearly identified among modern problems of hepatology and neuroscience in Ukraine. Despite the significant contribution to the development of lethal complications in patients with liver pathology and long history of the study of this issue, there is still no unified opinion on the links of HE pathogenesis. The aim of this review is to conduct a comprehensive analysis of current data on the spreading and mechanisms of development of HE. HE is a complex of potentially reversible neurocognitive disorders in patients with chronic or acute hepatic failure (ALF). HE is more often a complication of liver cirrhosis and is the second most frequent cause of hospitalization of such patients after ascites. When decompensating liver failure in acute or chronic hepatic pathology in patients severe forms of HE develop, accompanied by a progressive increase in intracranial pressure and the development of coma, which often ends lethal due to poor corrigibility of intracranial hypertension while maintaining hepatogenic neurointoxication. HE is considered as the end result of the accumulation of a number of neurotoxic substances in the brain, among which are ammonia, mercaptans, short chain fatty acids, false neurotransmitters, gamma-aminobutyric acid, manganese. The most popular among the reasons for the development of HE is the neurotoxic theory of ammonia. Ammonia is subjected to detoxification in the liver, turning into urea, a smaller fraction with the participation of glutamine synthetase is used in the synthesis of glutamine in muscles, liver and astrocytes of brain. In case of hepatic dysfunction and/or portosystemic shunting, the concentration of ammonia in blood increases up to 10 times and the main load for its detoxification is shifted to myocytes and astroglia. In ALF glutamine overload of astrocytes occurs with a change in intracellular osmolarity and subsequent edema of astroglia, which is accompanied by the development of cytotoxic edema of the brain. In this case, in astrocytes damaging of mitochondrial respiratory chain occurs and mitochondrial insufficiency develops, as well as processes of nitrosative-oxidative stress and oxidation of astrocytic and neuronal RNA, disruption of gene expression, synthesis of neuro- and gliotransmitters and synaptic plasticity. The increased influx of aromatic amino acids into brain leads to the synthesis of false neurotransmitters, which worsens serotoninergic, GABA-ergic, dopaminergic and glutamatergic neurotransmission. Damage to the components of the blood-brain barrier leads to aggravation of the water imbalance, penetration of hematogenous cytokines, endotoxins and other products of systemic inflammatory reaction into the cerebral parenchyma and development of neuroinflammation, which makes an important contribution to the further progression of cerebral edema. Conclusions: despite a comprehensive study of the problem, many open questions remain in the pathogenesis of HE. Special attention should be paid to more detailed study of the mechanisms of formation and elimination of edematous changes in brain tissue on the background of hepatogenic intoxication and the development of a systemic inflammatory reaction, the role of astroglia and its water channels in these processes, as well as the mechanisms of damage to the blood-brain barrier.